2004
DOI: 10.1249/01.mss.0000128163.88298.cb
|View full text |Cite
|
Sign up to set email alerts
|

Blood Volume Expansion and Cardiorespiratory Function: Effects of Training Modality

Abstract: These data indicate that: 1) 12 wk of CONT and INT result in similar improvements in VO2max, and LV function and 2) training-induced hypervolemia accounts for approximately 47% of the changes in VO2max after CONT and INT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
78
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 33 publications
6
78
1
3
Order By: Relevance
“…After examining 10 investigations that reported absence of blood volum expansion after training, they contended that exercise training elicits blood volume expansion [5]. In brief, we agree with Sawka et al [5] and Warburton et al [32] that the above-mentioned discrepancies are likely related to differences in participant sampling, experimental conditions and/or the season in which the research was conducted. For example, 10 weeks of moderate swimming in rats increased iron status, Hb and HCT, while strenuous swimming caused the variables to change in the opposite direction [34].…”
Section: Effects Of Exercise Training On the Erythrocytic Systemsupporting
confidence: 82%
See 2 more Smart Citations
“…After examining 10 investigations that reported absence of blood volum expansion after training, they contended that exercise training elicits blood volume expansion [5]. In brief, we agree with Sawka et al [5] and Warburton et al [32] that the above-mentioned discrepancies are likely related to differences in participant sampling, experimental conditions and/or the season in which the research was conducted. For example, 10 weeks of moderate swimming in rats increased iron status, Hb and HCT, while strenuous swimming caused the variables to change in the opposite direction [34].…”
Section: Effects Of Exercise Training On the Erythrocytic Systemsupporting
confidence: 82%
“…However, it has been found that both females and males exhibit similar erythrocytic adaptation to aerobic training. The total blood volume and erythrocyte volume in female endurance athletes were elevated compared to untrained controls [36], which was consistent with findings in males [32]. It is suggested that the typical response to endurance training is an increase in blood volume independent of gender [5].…”
Section: Effects Of Exercise Training On the Erythrocytic Systemsupporting
confidence: 74%
See 1 more Smart Citation
“…In fact, regular physical activity has been demonstrated to reduce abdominal adiposity and improve weight control (10)(11)(12), reduce triglyceride levels, increase high-density lipoprotein (HDL) cholesterol levels and decrease low-density lipoprotein (LDL)-to-HDL ratios (10,13), ameliorate glucose homeostasis and insulin sensitivity (14), lower blood pressure (BP) (15,16), improve autonomic tone (17,18), balance blood coagulation (19,20), augment coronary blood flow (21), improve cardiac function (22,23) and enhance endothelial function (24)(25)(26). Moreover, physical activity seems to play a fundamental role in the primary and secondary prevention of CVD modulating chronic inflammation as demonstrated by high circulating levels of inflammatory mediators that have been shown to be directly associated with most of the chronic diseases (1,27).…”
mentioning
confidence: 99%
“…Adults with mental illnesses have a mortality rate more than double that of the general population 27,28 , and a reduced life expectancy of between 10 and 20 years 28,29 . Evidence suggests , hormone production 74 , and cardiac efficiency 75 , and reduces systemic inflammation -a known precursor of many chronic conditions 76,77 . PA lowers metabolic risk factors of obesity, hypertension, dyslipidaemia, and hyperglycaemia in individuals without mental illness 78,79 ; these metabolic benefits of PA are similar for adults with mental illness 64,80 .…”
Section: Resultsmentioning
confidence: 99%